Computer-based instrumentation system for temperature measurement using thermocouple in MATLAB application - Jina, anak Muli (2008)
A computer- based instrumentation system has been developed for temperature measurement. The measurement is using thermocouple type K. Thermocouple will detect temperature then send the input to temperature transmitter. Temperature transmitter will accept the input from thermocouple or dc milivolt input and convert it to a 4 to 20mA signal for transmission. Then, the temperature transmitter connected to data acquisition (PCI1710HG) that used to read data from the temperature transmitter. SIMULINK model is use to interface DAQ with MATLAB. Analog input from DAQ will transfer to MATLAB Workspace. The system is developed with MATLAB Graphical User Interface (GUI). GUI will capture data from workspace and then calculated average of actual output and output error. The process is continued by plotting five point temperature calibrations and error curve. The system also can do the evaluation of the uncertainty of temperature measurement. Uncertainty of measurement is the doubt that exists about the result of any measurement. The system allowed the user to save the plot and key in the data in excel. By implementing this system in Industrial Instrumentation class, the improvement and continuity of learning process will be achieved.